A new species of Suwallia (Plecoptera: Chloroperlidae) from China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2015)
A new species of the genus Suwallia, S. wolongshana sp. nov. is described and illustrated from specimens collected in Sichuan Province, China. The new species is characterized by the two sclerotized bands between the hemitergal processes. The new species is the fourth recorded species of Suwallia from China.